STUDY ON THE PC LAN STTIBI - Misni Misni; Irwan Nimara, Ir (Jurnal Sistem Komputer, 1994)
Local Area Network (LAN) is a combination of computer and telecommunications technology as a means of exchange of information known as the Telecommunications Data. As a means of sharing data Telecommunications, LAN hardware performs as sharing and information sharing. Therefore, it can use hardware and software together. Means the ease of getting information for the LAN to get added value by speeding up information distribution and accessibility and besides the use of expensive peripherals can be used together.